Capture and use of water and radiation in summer intercrops in the south-east Pampas of Argentina - Coll, Leonardo (2012)
Intercrops are an alternative to intensify and diversify the agricultural systems in the south-east Pampas of Argentina. The aim of this study was to evaluate resource capture and resource use efficiency in maize–soybean and sunflower–soybean intercrops and in their respective sole crops. Water and radiation capture, biomass and grain production were measured for sole crops and intercrops. Water and radiation productivities were estimated as the energy produced per unit of annual available resource. Comparisons of intercrops with soybean sole crops were emphasized because current soybean expansion in the region represents a threat to agricultural system sustainability. Intercrops showed an increase in crop duration when compared to their sole counterparts. Maize–soybean intercrop resulted in an improved radiation and water productivities compared with soybean sole crops. Maize cultivated as sole crop attained the highest resource productivity. On the other hand, resource productivity of sunflower–soybean intercrop was higher than or similar to its corresponding sole crops. The improvement in water productivity for intercrop compared with soybean sole crop was accounted for by an increase in water capture efficiency and, also, by an increase in water use efficiency in the case of maize–soybean intercrop. The increase in radiation productivity for maize–soybean intercrop compared with soybean sole crop was the result of an increase in radiation use efficiency and of a minor but significant increase in radiation capture efficiency. Contrarily, the improvement in radiation productivity of sunflower–soybean intercrop compared with sunflower or soybean sole crops was null or small. Grain yield of intercropped sunflower and maize was 20% lower than yield of sole crops. Therefore, yield attained by intercropping was mainly limited by a poor production of the soybean component. This work provides eco-physiological basis to improve management practices of summer intercrops.